2020
DOI: 10.1111/pbi.13499
|View full text |Cite
|
Sign up to set email alerts
|

The celery genome sequence reveals sequential paleo‐polyploidizations, karyotype evolution and resistance gene reduction in apiales

Abstract: Summary Celery (Apium graveolens L. 2n = 2x = 22), a member of the Apiaceae family, is among the most important and globally grown vegetables. Here, we report a high‐quality genome sequence assembly, anchored to 11 chromosomes, with total length of 3.33 Gb and N50 scaffold length of 289.78 Mb. Most (92.91%) of the genome is composed of repetitive sequences, with 62.12% of 31 326 annotated genes confined to the terminal 20% of chromosomes. Simultaneous bursts of shared long‐terminal repeats (LTRs) in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 91 publications
(101 reference statements)
9
72
0
Order By: Relevance
“…The average contig N50 length was 13,040 bp, while the scaffold N50 length was 23,281 bp. In Apiaceae, the genome sizes of carrot, coriander, and celery were 421.5 Mb, 2118.31 Mb, and 3.33 Gb 33 35 , respectively. A total of 42,270 genes were identified in the genome of O. javanica , of which 93.92% of genes were functionally annotated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average contig N50 length was 13,040 bp, while the scaffold N50 length was 23,281 bp. In Apiaceae, the genome sizes of carrot, coriander, and celery were 421.5 Mb, 2118.31 Mb, and 3.33 Gb 33 35 , respectively. A total of 42,270 genes were identified in the genome of O. javanica , of which 93.92% of genes were functionally annotated.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic evolution process of gene families was constructed using CAFÉ version 3.1 with a probabilistic graphical model 35 . The evolutionary timescale was directly retrieved from http://www.timetree.org 64 and used to construct a primary phylogenetic tree.…”
Section: Methodsmentioning
confidence: 99%
“…= not specified). Of these, four genomes are finely assembled into pseudomolecules (i.e., chromosomes, Apium graveolens [98], Daucus carota [76], Centella asiatica [99] and Coriandrum sativum [100]); whereas the others (Angelica gigas, Oenanthe javanica, Bupleurum falcatum and Foeniculum vulgare) were incomplete and/or assembled at the scaffold level [46,96,97,101]. While the latter were obtained exclusively through short reads sequencing, the first four resulted from a combination of second-and third-generation sequencing platforms, proving to be the most suitable approach for obtaining fully assembled, highly accurate genome sequences.…”
Section: Whole Genome Sequencing Provides Powerful Tools For Marker-assisted Breedingmentioning
confidence: 99%
“…The same species are inflorescence-rich in secondary metabolites, while another RNA-seq analysis was aimed at the identification of genes involved in terpenoid and brassinosteroid accumulation [118]. Coumarins and coumarin-derived compounds (e.g., furanocoumarins) play a repulsive and toxic role against certain insect larvae, and the key genes involved in their biosynthesis have been greatly investigated in Pastinaca sativa [119], Angelica dahurica [120] and Apium graveolens [98]. In particular, Munakata et al identified two different prenyltransferases (PT1 and PT2) responsible for the synthesis of the two furanocoumarin isomers (linear and angular) in P. sativa [119]; whilst Zhao et al and Song et al elucidated the seven enzymes leading to coumarin production in A. dahurica and A. graveolens, respectively [98,120].…”
Section: Rna-seq Analyses Are Starting Points For the Identification Of Genes Responsible For Traits Of Agronomic Interestmentioning
confidence: 99%
See 1 more Smart Citation